Extensive scabies infestation in a stateless and marginalized Bajau Laut boy - Sani, Huzairi; Mohamed Tahir, Ahmad Rashidi; Parthiban, Nirmalatiban; Helmi Salim, Ahmad Munawwar (International Journal of Human and Health Sciences (IJHHS), 2022)
The Bajau Laut people are sea gypsies, who are stateless and marginalized populations. A young boy was brought to an outreach clinic with symptoms of body itchiness. He has 3 other siblings who also have the similar symptom. Clinically, the rash was extensive with erythematous papules, excoriations and eczematous features involving the trunk, thighs, buttocks, genitalia, and bilateral feet giving the diagnosis of scabies. He was prescribed topical Permethrin 1% Lotion to be applied at night from the neck down and left on until the next morning. Management of such transmissible skin disease caused by Sarcoptes Scabiei has been a great challenge among indigenous communities. This case report provides an insight into the possible challenges faced by clinicians in detecting and managing scabies infection among the indigenous and under-researched population in Malaysia. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 445-448